Exploring How Work Motivation and Non-Monetary Compensation Affect Employee Performance: Insights from a Packaging Section in a Chemical Company in Bandung - Rudi Gunawan; Senen Machmud; Ester Manik; Nenny Rinawati (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2025)
This research addresses the critical issue of how motivation and indirect compensation affect employee performance in a packaging division of a chemical company located in Bandung. The study aims to analyze these relationships and their implications for enhancing workplace productivity. To achieve this goal, the research employs a mixed-method approach, utilizing questionnaires, observations, and literature studies to gather relevant data. The analysis employs multiple linear regression techniques, supported by hypothesis testing through F-tests and T-tests, based on a sample of 53 respondents selected using incidental sampling. The findings reveal that both motivation and indirect compensation significantly influence employee performance, both individually and collectively, within the packaging division of the chemical company in Bandung. This study's implications suggest that organizations should prioritize enhancing motivation and optimizing compensation strategies to improve employee performance effectively. Additionally, the research contributes to the existing literature on workplace dynamics by providing empirical evidence of the importance of these factors in a specific industrial context, thereby offering valuable insights for managers and HR practitioners in similar sectors.